Prevalence Assessment of Feline Infectious Peritonitis Based on Rapid Test and Protein Ratio Analysis in Dhaka, Bangladesh - Rupsana Perven Borsha; Maruf Hasan; M A Zabbar; Md Roknuzzaman Khan; Md Akib Zabed; Al Wasef; Md Mahedi Hassan; Gopal Chandra Das (Research in Agriculture Livestock and Fisheries, 2025)
Feline Infectious Peritonitis (FIP) is a fatal systemic disease of domestic cats caused by a virulent mutant feline coronavirus (FCoV). Despite its global significance, epidemiological data on FIP in Bangladesh remain scarce. This study aimed to determine the prevalence, clinical patterns, and key risk indicators of FIP among domestic cats in Dhaka from January to May 2025. A total of 300 cats of various breeds (local, Persian, and mixed) presented to veterinary clinics were enrolled with owner consent under a cross-sectional study design. Rapid antigen detection (Testsealabs, China) was used for initial screening, and the albumin-globulin (A/G) ratio was assessed as a supportive diagnostic tool. FIP was confirmed in 200 cats (66.67%). Mixed-breed (50%) and local cats (33.33%) accounted for the majority of positive cases. The highest prevalence was observed in the 60–120-day age group. Female cats demonstrated higher infection and fatality rates, whereas male cats showed comparatively better recovery outcomes. Clinically, the dry form (48%) and wet form (40%) were most commonly observed, with the wet form exhibiting the highest fatality rate (67.5%). Protein profiling revealed that 82 cats-predominantly female local breeds-had a markedly low A/G ratio (<0.4), strongly supporting FIP infection. These findings highlight a considerable burden of FIP among domestic cats in Bangladesh and underscore the urgent need for improved diagnostic surveillance, greater owner awareness, and enhanced management practices to mitigate its impact. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 427-436